EMPIRICAL AND SPATIAL RELATION BETWEEN MAGNETIC AND RADIOMETRIC SURVEY OVER MICA SCHIST AREA, OGUN STATE, NIGERIA - Ogunsanwo, Fidelis Olatoyosi; Mustapha, Amidu Olalekan; Ozebo, Vitalis Chidi; Okeyode, Itunu Comfort; Ayanda, Jacob Dele; Sanni, Kikelomo Racheal (FUDMA Journal of Sciences, 2025)
The integration of magnetic and radiometric methods has received limited attention in mica schist terrains, despite their complementary sensitivity to lithological and geochemical variations. This study addresses this gap by jointly applying magnetic measurements and soil radiometric analyses over the mica deposit zone of Area J4, Ogun State, Nigeria. The magnetic surveys capture variations in rock magnetization, while radiometric surveys quantify radioelement concentrations (U, Th, K), and their empirical integration enables a more robust characterization of subsurface heterogeneity. The results demonstrate strong positive correlations between magnetic intensity and radioelement concentrations, with regression models confirming direct proportional relationships. This finding highlights the predictive capacity of integrated geophysical datasets, whereby one survey can be used to infer or validate anomalies detected by the other. Spatial contour mapping further delineated coincident magnetic–radiometric anomalies, strengthening the case for exploration targets associated with radioelement-rich mineralization. Beyond local outcomes, this study emphasizes the broader value of multi-method geophysics in mineral exploration. By establishing empirical relationships between datasets, interpretational ambiguities are reduced, anomaly discrimination is improved, and the efficiency of resource targeting is enhanced. Such integrative approaches are particularly relevant in complex Precambrian terrains, where single-method surveys may overlook subtle but economically significant signals. Methodological limitations include the restricted survey coverage and focus on near-surface soil samples, which may not fully represent deeper lithological variations. Conclusively, this study have demonstrates the scientific and practical relevance of integrating magnetic and radiometric methods as a predictive framework for mineral exploration and geophysical mapping.
Keywords: Radioelement; Model; Inferential; Anomalous; Spatial